Accupuncture-like transcutaneous electrical nerve stimulation therapy success using a commercially available unit 8 years post-radiation for xerostomia: a case report. Issue 2 (8th May 2017) - Iovoli, Austin J.; Singh, Anurag K.
Abstract: Background: Accupuncture-like transcutaneous electrical nerve stimulation (ALTENS) therapy has been shown in prospective studies to be effective in the treatment of radiation-induced xerostomia. Those studies treated patients within 27 months from end of radiation with ALTENS delivered in the clinic using a Codetron unit. However, that unit is no longer produced and there is limited data on success of ALTENS when delivered at home. Methods: A 50-year old man with xerostomia, 8 years post-radiation for T4N1 squamous cell carcinoma of the tonsillar fossa, was given ALTENS with a currently commercially available unit from Girish Surgical. He used the unit at home, 20 minutes daily for 8 weeks. Results: After 8 weeks of ALTENS therapy the patient saw a reduction in the Self-Reported University of Michigan Xerostomia-Related Quality of Life Scale from 20 to 1. Conclusion: This case report demonstrates (1) the Girish Surgical unit is effective, (2) self-administration of ALTENS in patients who cannot come to clinic regularly may be practical and (3) ALTENS can still offer durable benefit to patients even 8 years after chemoradiation therapy.